Economic efficiency of spring false flax growing in Pricarpattya region - Григорів, Я. Я. (Scientific Progress & Innovations, 2012)
The article deals with results of investigations from 2009- 2011 in a stationary field experiments on sod-podzol soils concerning the study the effectiveness of various growing technologies on spring false flax productivity and thus the economic efficiency of this crop growing. The dependence of elements of crop yield and productivity on the use of mineral fertilizers has been found out. It has been concluded that fertilization had a significant impact on seed productivity of spring false flax and on the rate of cost and profitability of spring false flax seeds.